(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2023)
This semantic analysis explores the depth of meaning and cultural significance embedded within ethnographisms associated with English funeral ceremonies. Through a meticulous examination of key terms, this analysis unveils the layers of symbolism, emotion, and cultural context inherent in these linguistic constructs. The study reveals that these terms are not merely linguistic expressions but carry profound semantic weight, symbolizing the reverence, continuity, and shared experiences that define English funeral ceremonies.